2012
DOI: 10.1038/onc.2012.45
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogen-specific mutational and epigenetic alterations in INK4A, INK4B and p53 tumour-suppressor genes drive induced senescence bypass in normal diploid mammalian cells

Abstract: Immortalization (senescence bypass) is a critical rate-limiting step in the malignant transformation of mammalian somatic cells. Human cells must breach at least two distinct senescence barriers to permit unfettered clonal evolution during cancer development: (1) stress- or oncogene-induced premature senescence (SIPS/OIS), mediated via the p16-Rb and/or ARF-p53-p21 tumour-suppressive pathways, and (2) replicative senescence triggered by telomere shortening. In contrast, because their telomerase is constitutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 49 publications
0
53
0
Order By: Relevance
“…In the same study, IFNγ methylation was not altered, in contrast to the above-mentioned study [50]. Hypermethylation of the promoter region of p16 was evident in B a P-induced primary immortalized Syrian hamster dermal fibroblasts, accompanied by an overexpression of the gene [54]. …”
Section: Epigenetic Effects Associated With Carcinogenic Chemicalsmentioning
confidence: 84%
“…In the same study, IFNγ methylation was not altered, in contrast to the above-mentioned study [50]. Hypermethylation of the promoter region of p16 was evident in B a P-induced primary immortalized Syrian hamster dermal fibroblasts, accompanied by an overexpression of the gene [54]. …”
Section: Epigenetic Effects Associated With Carcinogenic Chemicalsmentioning
confidence: 84%
“…The multi-step tumourigenesis model starting with a dysregulated epigenetic progenitor cell is in keeping with observations made in cultured primary Syrian hamster dermal fibroblasts transiently exposed to benzo[ a ]pyrene or nickel chloride (a non-mutagenic carcinogen) [294]. The in vitro exposures generated immortal variants that could be selected for continued growth after senescence of the bulk culture of primary cells (at around 50 passages).…”
Section: Experimental Evidence From In Vitro Cell Transformation Mmentioning
confidence: 60%
“…Similarly, O 6 -methylguanine DNA methyltransferase (MGMT), an enzyme that repairs O 6 -methylguanine, was silenced by promoter hypermethylation in NiS-transformed human bronchial epithelial (16HBE) cells [47]. Recent studies on the Syrian hamster (SHD) cell lines immortalized by soluble nickel demonstrated that hypermathylation of CpG cluster immediately upstream of p16 exon 1 resulted in p16 gene silencing and consequent cell senescence bypass [48]. …”
Section: Nickel and Gene Silencingmentioning
confidence: 99%